Shedding of infectious SARS-CoV-2 in two asymptomatic children - Rodriguez, Pamela Elizabeth (2023)
Asymptomatic infections with SARS-CoV-2 are associated with viral transmission and have a key role in the propagation of the pandemic. Understanding viral shedding during asymptomatic infections is critical. Unfortunately, data on asymptomatic SARS-CoV-2 infection in children is extremely limited. To determine the presence of viral viable shedding, we prospectively followed two healthy children of a family where both parents developed mild COVID-19 (April 2021). SARS-CoV-2 detection was made by RT-PCR and virus isolation by cell culture from saliva samples. Positive samples were sequenced to identify variants of SARS-CoV-2. Serum samples were evaluated to determine the presence of antibodies using a single enzyme-linked immunosorbent assay (ELISA, COVIDAR IgG). Both children were SARS-CoV-2 positive and asymptomatic. In addition, the virus grew in cell culture from saliva samples. Furthermore, one child showed viable SARS-CoV-2 for at least 17 days after the onset symptoms from his father. The recommended isolation period for asymptomatic contacts during the acquisition of data had been established for 10 days; however, this child remained with viable virus beyond that period. The positive samples from both children were consistent with B.1.1.28.1 lineage (Gamma). In both asymptomatic children, anti-Spike IgG was detected. Asymptomatic children may represent a source of infection that should not be underestimated during this pandemic.